Cyclooxygenase-2 Inhibition as an Add-On Strategy in Drug Resistant Epilepsy—A Canine Translational Study - Fischer, Andrea; Hülsmeyer, Velia-Isabel; Munoz Schmieder, Viviana P.; Tipold, Andrea; Kornberg, Marion; König, Florian; Gesell, Felix K.; Ahrend, Liza K.; Volk, Holger A.; Potschka, Heidrun (Frontiers in Veterinary Science, 2022)
Drug resistant epilepsy is a common complaint in dogs and affects up to 30% of dogs with idiopathic epilepsy. Experimental data suggest that targeting cyclooxygenase-2 (COX-2) mediated signalling might limit excessive excitability and prevent ictogenesis. Moreover, a role of COX-2 signalling in seizure-associated induction of P-glycoprotein has been described. Thus, targeting this pathway, may improve seizure control based on disease-modifying effects as well as enhancement of brain access and efficacy of co-administered antiseizure medication. The present open-label non-controlled pilot study investigated efficacy and tolerability of a COX-2 inhibitor (firocoxib) add-on therapy in a translational natural occurring chronic epilepsy animal model (client owned dogs with phenobarbital-resistant idiopathic epilepsy). The study cohort was characterized by frequent tonic-clonic seizures and cluster seizures despite adequate phenobarbital treatment. Enrolled dogs (n=17) received a firocoxib add-on therapy for 6 months. Tonic-clonic seizure and cluster seizure frequencies were analysed at baseline (6 month) and during the study (6 month). Responders were defined by a substantial reduction of tonic-clonic seizure and cluster seizure frequency (≥ 50%). Eleven dogs completed the study and were considered for statistical analysis. Two dogs (18%, 2/11) were classified as responders based on their change in seizure frequency. Interestingly, those two dogs had the highest baseline seizure frequency. The overall tolerability was good. However, given the low percentage of responders, the present data do not support an overall considerable efficacy of COX-2 inhibitor add-on therapy to overcome natural occurring phenobarbital-resistant epilepsy in dogs. Further translational evaluation should only be considered in canine patients with a very high baseline seizure density